Educational Values in the Diversity of Javanese Traditional Ceremonies among Pendalungan Community - Yerry Mijianti (Javanologi: International Journal of Javanese Studies, 2023)
This study aims to describe educational values in the diversity of Javanese traditional ceremonies among Pendalungan community. The design chosen was ethnography. Ethnographic study is carried out in six stages, namely (1) formulating problems, (2) selecting cases, (3) obtaining entry points, (4) collecting data, (5) analyzing data, and (6) reporting findings. Subjects and locations for the study were determined with purposive sampling technique. The subjects are people who are considered to have quality and are able to provide information about Javanese traditional ceremonies. The study was conducted in seven sub-districts, namely Wuluhan, Umbulsari, Sukowono, Tanggul, Tempurejo, Ambulu, and Pakusari. Data were collected by means of observation, interviews, documentation, and audio-visual materials. The data were analyzed in six stages, namely: (1) organizing and preparing the data for analysis, (2) carefully reading all the data, (3) coding the data, (4) describing the data, (5) representing the data in a qualitative narrative, and (6) interpreting data. The validity of the data is obtained by extending working time and observing and triangulating methods, sources, and theories. As a result, the Javanese traditional ceremonies performed by the Pendalungan community are very diverse because the character of the Pendalungan community, one of which is open to change and easy to adapt, makes the implementation of Javanese traditional ceremonies adapted to environmental conditions, natural conditions, tools, materials, and performers of the ceremonies. The diversity in the implementation of Javanese traditional ceremonies by the Pendalungan community has values, namely religious, nationalist, independent, mutual cooperation, and integrity